Understanding the aerodynamic environment in track cycling - Fitzgerald, S. (School of Mechanical Engineering, The University of Adelaide, 2022)
This research pro ject aims to improve our understanding of the aerodynamic environment experienced by a track cyclist within an indoor velodrome. This has been completed through the use of an in-situ experimental setup and the development of theoretical calculations for salient measurements. By developing an understanding of the aerodynamic environment, we can improve the accuracy of theoretical modelling and help develop new methods of bicycle and/or rider drag reduction. The primary method for conducting this research was the development of an instrumented bicycle that can measure the incident airflow, roll angle, steering angle, and power output as a cyclist rides around a velodrome. A quasi-steady theoretical analysis of the airflow encountered by a cyclist travelling around a bend was created that indicates a yaw and pitch angle relative to the cyclist. A new model of velodrome geometry that includes transition curves into and out of the bends was also developed to improve the accuracy of theoretical calculations. Measurements of the roll and steering angles were completed and compared to theoretical calculations, including the effects of the bend transitions. The instrumented bicycle was also used to measure data in a velodrome with and without other riders. It is found that the relative airflow experienced by a cyclist in an indoor velodrome deviates from a direct headwind due to three primary factors. Firstly, there is the position of the rider in the lap, with curved airflow arising when cornering/leaning on the bends. Secondly, there are several effects due to the rider's pedalling which can have a combination of influences, namely, rocking the bicycle side to side, steering the front wheel left to right, and the motion of the legs producing an upstream aerodynamic effect. Thirdly, there is an influence from other riders on the track, ranging from a large decrease in the airspeed when drafting directly behind a rider to a smaller influence from other riders when in their far wake. Turbulence measurements using iii the instrumented bicycle show that other riders on the track can alter the freestream turbulence experienced by a cyclist, even when other riders are half a lap ahead. Measurements of the flow through the middle of the bicycle frame were undertaken in a velodrome with a live rider, in a wind tunnel with an anatomically-accurate pedalling mannequin, and with potential flow calculations. The three different methods of experimentation all demonstrated a large deviation of ±15? of yaw angle due to the position and movement of the pedalling legs. A minor reduced-frequency effect was observed, indicating that the magnitude of the cadence can influence the aerodynamic results and the pedalling motion cannot be assumed to be quasi-steady at high cadences. The work undertaken in this project helps to provide a greater understanding of the flow experienced inside an indoor velodrome and provides validation of commonly used theoretical calculations. It can be used as a first step towards the understanding and reduction of the differences between wind tunnel and field testing.